Pain in older adults over the age of 80: Characteristics, impacts and coping strategies - Atílio, Fernando Gustavo Cordeiro; Suzuki, Augusto Furukawa; Damaceno, Daniela Garcia; Alarcon, Miriam Fernanda Sanches; Marin, Maria José Sanches; Girotto, Marcos Antonio (Revista Cuidarte, 2021)
Introduction: The prevalence of chronic pain has exponentially increased as a consequence of aging worldwide, particularly in older adults, which is related to changes in aging senescence. The objective of this research is to describe the presence of pain, characteristics and coping strategies among older adults over the age of 80. Materials and Methods: A quantitative descriptive exploratory study was conducted by collecting data through the Brief Pain Inventory instrument, in addition to sociodemographic data of 60 adults aged 80 and older who lived in the area of influence of a Family Health Strategy team in a municipality of the center-west region of São Paulo. Results: The final sample included 60 older adults aged 85.2 on average who were mostly women (64%), widowed (67%), white (82%), retired (67%) and having complete primary education (32%). Among the participants, 73% reported pain during the last week with significant repercussions on their daily life. Lower extremity pain was commonly reported interfering with their performance in daily activities in a moderate or severe manner. 48% of older adults use pharmacological and non-pharmacological methods for pain relief with satisfactory results. Conclusions: Coping with pain in older adults requires a multifactorial and comprehensive approach involving both interdisciplinary care and family support. While the prevalence of pain among adults over the age of 80 is higher, interfering with their daily life, they find pain relief by using pharmacological and non-pharmacological methods. How to cite this article: Atílio, Fernando Gustavo Cordeiro; Suzuki, Augusto Furukawa; Damaceno, Daniela Garcia; Alarcon, Miriam Fernanda Sanches; Marin, Maria José Sanches; Girotto, Marcos Antonio. Dor no idoso acima de 80 anos: características, impactos e estratégias de enfrentamento. Revista Cuidarte. 2021;12(2):e1310. http://dx.doi.org/10.15649/cuidarte.1310